Speleonectes kakuki, a new species of Remipedia (Crustacea) from anchialine and sub-seafloor caves on Andros and Cat Island, Bahamas - Daenekas, Jana; Iliffe, Thomas M.; Yager, Jill; Koenemann, Stefan (Zootaxa, 2009)
A new species of the crustacean class Remipedia is described, illustrated and compared to closely related taxa. Speleonectes kakuki n. sp. inhabits at least four widely separated anchialine cave systems on the Great Bahama Bank. A total of ten specimens were collected from caves on Andros and Cat Island. Speleonectes kakuki can be distinguished from other species of remipedes by the presence of heteromorphic sternal bars and comparatively robust and pilose prehensile cephalic limbs. It is the first remipede to be collected from an offshore cave, whereas as all previously known remipede habitats are inland sites. The presence of remipedes in sub-seafloor caves is highly significant in that it suggests the anchialine habitat is much more extensive than previously thought and may extend for hundreds of kilometers beneath the shallow waters of limestone banks to link widely separated inland caves.